2016
DOI: 10.3382/ps/pew083
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and metabolism of dietary guanidino acetic acid fed to broilers

Abstract: In two feeding experiments the retention of supplemental guanidine acetic acid (GAA) in broilers was investigated. In both experiments, the same three treatments were used; the basal feed was supplemented with 0, 0.6, or 6.0 g GAA per kg of feed. While in a growth study (experiment 1) day-old, male Ross 308 broilers were fed diets for 35 days, these diets were fed for only 8 days to fistulated broilers 34 days of age in a balance study (experiment 2). Feeding 0.6 g/kg GAA did not improve growth performance whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…Findings showed that GAA addition to diet had not significant effects on productive performance but 0.171% GAA addition decreased egg weight from 2 th week to [24,25] . However, Michiels et al [7] observed only slightly increase in FI of broiler chicks fed with GAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings showed that GAA addition to diet had not significant effects on productive performance but 0.171% GAA addition decreased egg weight from 2 th week to [24,25] . However, Michiels et al [7] observed only slightly increase in FI of broiler chicks fed with GAA.…”
Section: Discussionmentioning
confidence: 99%
“…FCR was no influenced by GAA treatments and positive control (2% meat meal); showing that creatine supplementing from each source had not significant effect on the mentioned parameter. Tossenberger et al [24] stated that GAA addition to diet had not significant effect on FCR of broiler chicks. Other studies have shown that GAA addition to diet lowered FCR in broiler chicks [2,5,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the present average live weights were less than 2000 g after 60 days' growth, and this may be related to the genetics of the broilers (female Partridge-Shank) used in the present trial. Lemme et al (2007a) reported that the optimum supplemental concentration of GAA ranged from 0.6 to 1.2 g/kg DM of feed, whereas 6.0 g/kg GAA would reduce feed consumption and consequently weight gain (Tossenberger et al, 2016). These reasons Results are means of six pens corresponding to 30 broilers for each treatment.…”
Section: Growth Performance Of Broiler Response To Dietary Supplementmentioning
confidence: 99%
“…Guanidinoacetic acid (GAA), as a creatine precursor, has received growing attention in poultry nutrition, mainly because most of the current poultry diets formula are relying on vegetable products, which compared to animal-based ingredients are devoid of creatine (Michiels et al 2012). Creatine and its metabolite, phosphocreatine, are used to replenish adenosine triphosphate (ATP) to prevent the energy depletion of the cells (Tossenberger et al 2016). After the synthesis of GAA in the kidneys, through the catalytic effect of arginine: glycine amidinotransferase, GAA is transferred to the liver for the conversion to creatine.…”
Section: Introductionmentioning
confidence: 99%